Effect of visible light on the removal of trichloromethane by graphene oxide - Ulucan-Altuntas, Kubra; Debik, Eyup; Ustundag, Cem Bulent; Guven, Miray Deniz; Gocen, Kubra Ayca (ELSEVIER SCIENCE SA, 2020)
In this experimental study, the degradation of disinfection by-products using graphene oxide was studied. Degradation of chloroform, which is the most common type of trihalomethanes in water, was investigated. Graphene oxide (GO) was synthesized by the Modified Hummers' Method. TEM images showed that the synthesized graphene oxide was exfoliated layer by layer and was very stable according to the zeta potential result. In the degradation studies; the effect of time, chloroform concentration and graphene oxide concentration were investigated both under visible light and under darkness. According to the experimental results, studies containing 100 mu g/L trichloromethane and 250 mg/L GO were stabilized after 30 min and the removal of 70.6% for darkness increased to 98% under visible light. When the graphene oxide concentration is increased, it is seen that the positive effect of visible light increases from 22% to 30%. According to the isotherm and kinetic model research, it was found that the studies conducted in both conditions were appropriate to Freundlich isotherm and Pseudo second-order kinetic model. The maximum adsorption capacities based on Pseudo second-order kinetic modeling was obtained as 350 and 450 mu g/g for darkness and visible light, respectively.
Keywords: Trihalomethane; Trichloromethane; Chloroform; Graphene oxide; Nanoparticle; Photocatalytic degradation; Adsorption; BISPHENOL-A; METAL OXIDE; DEGRADATION; CARBON; PERFORMANCE; IRRADIATION; MECHANISM; KINETICS; MODELS; Materials Science; Physics